The Power of Words: Decoding the Nexus of Impression Management Tactics in South African SOEs' Annual Reports that Shape Stakeholder Perception - Ngcizela, Andiswa; Phesa, Masibulele; Arulanandam, Benedict Valentine (Yayasan Ilomata, 2024)
This topic investigates the nexus, between textual features in chairperson’s reports and their effectiveness in shaping stakeholder perceptions in South African SOEs. These voluntary sections are prone to manipulation to mask poor governance and maladministration. SOEs are key to South Africa’s economic development, but their declining performance prompted this analysis. Using secondary data from SOEs’ annual reports, a quantitative content analysis approach was applied. Signaling theory guided interpretation. The study examined the chairperson’s report by analyzing variables such as report length, positive and negative sentiments, personal references, and passive language in both profitable and non-profitable SOEs. Findings showed both profitable and non-profitable SOEs use impression management. Profitable SOEs had longer reports and more words, but report length differences were not significant. Profitable SOEs also used more personal references, though marginally. Both categories employed a similar proportion of positive tone, surpassing negative tone. Non-profitable SOEs used more passive voice, but the difference was minimal. This study highlights how signaling theory applies to public sector disclosures, offering insights for stakeholders into how impression management may shape the presentation of SOE performance. It aids users in recognizing tactics used by SOEs to maintain relevance amid persistent poor outcomes.